2000
DOI: 10.1080/07328300008544129
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active 1-Aminodeoxy and 1-O-Alkyl Derivatives of The Powerful D-Glucosidase Inhibitor 2,5-Dideoxy-2,5-Imino-D-Mannitol

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Azido alcohol 25 (Scheme 4) appeared to be a suitable choice,15 and after deprotonation with sodium hydride, the alkoxide reacted with mesylate 5 to give azido ether 26 in 89% yield 16. To install the C10 axial alcohol, the more electron-rich endocyclic double bond was first selectively dihydroxylated using Sharpless's asymmetric dihydroxylation conditions 7b,7e,17.…”
Section: Resultsmentioning
confidence: 99%
“…Azido alcohol 25 (Scheme 4) appeared to be a suitable choice,15 and after deprotonation with sodium hydride, the alkoxide reacted with mesylate 5 to give azido ether 26 in 89% yield 16. To install the C10 axial alcohol, the more electron-rich endocyclic double bond was first selectively dihydroxylated using Sharpless's asymmetric dihydroxylation conditions 7b,7e,17.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15] They found that one-step N-derivatization of amine derivative 2 led to the generation of powerful β-glycosidase inhibitors, whereas aminoiminohexitol 2 itself was a moderate β-glucosidase inhibitor. [10,11,14] More recently, Ramesh and co-workers prepared several selective glycosidase inhibitors based on modifications to l-ido aza-sugar 3. [16] While the parent compound showed no glycosidase inhibitory activity, N-tosyl, N-methyl, and N-ethyl derivatives all exhibited good, and often selective, activity against the glycosidases tested.…”
Section: Introductionmentioning
confidence: 98%
“…Here, the Amadori rearrangement formed a key part of their synthetic strategy. [48][49][50][51][52][53] Stütz and Wrodnigg found that the one-step N-derivatisation of amine-derivative (12) led to the generation of powerful β-glycosidase inhibitors, while amino imino-hexitol 12 itself was a moderate β-glucosidase inhibitor. 48,49,52 More recently, Ramesh and co-workers prepared several selective glycosidase inhibitors based on modifications to the L-ido azasugar 13.…”
Section: Amino-imino-hexitols As Glycosidase Inhibitorsmentioning
confidence: 99%
“…[48][49][50][51][52][53] Stütz and Wrodnigg found that the one-step N-derivatisation of amine-derivative (12) led to the generation of powerful β-glycosidase inhibitors, while amino imino-hexitol 12 itself was a moderate β-glucosidase inhibitor. 48,49,52 More recently, Ramesh and co-workers prepared several selective glycosidase inhibitors based on modifications to the L-ido azasugar 13. 54 While the parent compound showed no glycosidase inhibitory activity, N-tosyl, N-methyl, and N-ethyl derivatives all exhibited good, and often selective, activity against the glycosidases tested.…”
Section: Amino-imino-hexitols As Glycosidase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation